Functional Characterization of TaSnRK2.8 Promoter in Response to Abiotic Stresses by Deletion Analysis in Transgenic Arabidopsis - Zhang, Hongying; Jing, Ruilian; Mao, Xinguo (Frontiers in Plant Science, 2017)
Drought, salinity, and cold are the major factors limiting wheat quality and productivity; it is thus highly desirable to characterise the abiotic-stress-inducible promoters suitable for the genetic improvement of plant resistance. The sucrose non-fermenting 1-related protein kinase 2 (SnRK2) family genes show distinct regulatory properties in response to abiotic stresses. The present study characterized the approximately 3000-bp upstream sequence (the 313 bp upstream of the ATG was the transcription start site) of the Triticum aestivum TaSnRK2.8 promoter under abscisic acid (ABA) and abiotic stresses. Four different-length 5′ deletion fragments of TaSnRK2.8 promoter were fused with the GUS reporter gene and transformed into Arabidopsis. Tissue expression analysis showed that the TaSnRK2.8 promoter region from position −1481 to −821 contained the stalk-specific elements, and the region from position −2631 to −1481 contained the leaf- and root-specific elements. In the ABA-treated seedlings, the deletion analysis showed that the TaSnRK2.8 promoter region from position −821 to −2631 contained ABA response elements. The abiotic stress responses of the TaSnRK2.8 promoter derivatives demonstrated that they harboured abiotic-stress response elements: the region from position −821 to −408 harboured the osmotic-stress response elements, whereas the region from position −2631 to −1481 contained the positive regulatory motifs and the region from position −1481 to −821 contained the leaf- and stalk-specific enhancers. Further deletion analysis of the promoter region from position −821 to −408 indicated that a 125-bp region from position −693 to −568 was required to induce an osmotic-stress response. These results contribute to a better understanding of the molecular mechanisms of TaSnRK2.8 in response to abiotic stresses, and the TaSnRK2.8 promoter seems to be a candidate for regulating the expression of abiotic stress response genes in transgenic plants.